Synthesis of Zeolitic Imidazolate Framework-8 from Waste Electrodes via Ball Milling for Efficient Uranium Removal - Minhua Su; Jinyao Zhu; Ruoning Wu; Jiaqi Pan; Jingran Yang; Jiaxue Zhao; Diyun Chen; Changzhong Liao; Kaimin Shih; Shengshou Ma (Separations)
Developing a cost-effective approach for the remediation of wastewater containing uranyl [U(VI)] ions is essentially important to ecosystems and human health. In this study, a Zn-based ZIF-8 framework was fabricated from wasted batteries through an environmentally friendly ball milling process featuring a distinct microstructure compared to those synthesized from commercial Zn(II) sources. The as-obtained Zn-based ZIF-8 framework can effectively remove U(VI) ions from water, and a high removal efficiency of up to 99% is achieved across different process parameters, including initial dosage, pH values, and the presence of interfering ions. The superior U(VI) removal performance is attributed to the synergistic effect of microstructural features (e.g., crystallite size, specific surface area and pore diameter) and chemical interaction within the framework of Zn-based ZIF-8, resulting in the formation of the U···N chelates. This study integrates waste upcycling and hazardous U(VI) removal in an environmentally sound way, thereby promoting a circular economy.